1985
DOI: 10.1172/jci112241
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D increases calmodulin binding to specific proteins in the chick duodenal brush border membrane.

Abstract: In previous studies we demonstrated that the biologically active

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The high degree of localization suggests the existence of high capacity Ca-binding components. Other studies (Bikle and Munson 1985;Bikle et al 1984;Kaune et al 1994) have suggested a possible role for this complex in the 1,25(OH) 2 D 3 -stimulated Ca uptake across the brush border membrane. Much of the brush border calmodulin is known to be associated with a 110-kDa (variously reported as 102-110 kDa) calmodulin-binding protein, the brush border myosin I, which exhibits ATPase activity and mechanoenzyme properties (Mooseker et al 1991).…”
Section: Discussionmentioning
confidence: 91%
“…The high degree of localization suggests the existence of high capacity Ca-binding components. Other studies (Bikle and Munson 1985;Bikle et al 1984;Kaune et al 1994) have suggested a possible role for this complex in the 1,25(OH) 2 D 3 -stimulated Ca uptake across the brush border membrane. Much of the brush border calmodulin is known to be associated with a 110-kDa (variously reported as 102-110 kDa) calmodulin-binding protein, the brush border myosin I, which exhibits ATPase activity and mechanoenzyme properties (Mooseker et al 1991).…”
Section: Discussionmentioning
confidence: 91%
“…4 and Ref. 2) may result from the more highly purified nature of luminal and basolateral membrane preparations. Moreover, the presence of renal CaMBP-D110 in luminal membranes suggests that this CaMBP-D may be similar to 110-kDa chick intestinal BBM 1 (5,6,21). However, whether there is any association of luminal membrane CaMBP-D74 with CaMBP-D110 and its functions remains a question for future studies.…”
Section: Discussionmentioning
confidence: 98%
“…2). Two CaMBPs related to functions of vitamin D (4,5,12,22,46) were previously localized to specific cellular membrane poles, i.e., the 136-kDa plasma membrane Ca 2ϩ -ATPase in renal basolateral membranes (8,19,35) and the 110-Da brush-border myosin 1 (BBM 1) protein in luminal membranes of chick intestinal cells (5, 6, 21). Thus it was important to determine whether the CaMBP-Ds could be detected in purified renal basolateral and luminal membrane preparations.…”
Section: Discussionmentioning
confidence: 99%
“…1,25-(OH)2D3 did not increase TSH secretion induced by K+ depolarisation. induc¬ tion of transcellular calcium transport (Bikle & Munson 1985). This could indicate that l,25(OH)2D3 enhances the mecha¬ nism responsible for the TRH-induced TSH re¬ lease.…”
Section: Discussionmentioning
confidence: 99%